«Kyiv-Pechersk Patericon» as the Fountainhead of the Ancient Ukrainians’ Linguistic Image of the World (Linguostylistic Studies, 2017)
The article highlights the the importance of the «Kyiv-Pechersk Patericon»for the spiritual culture of the Ukrainian society. In the focus of attention are the peculiarities of the lexical intepretation of the basic existential notions life and death in the conceptual sphere of the ancient Ukrainians. The study has determined their semantic structure and their usage dynamics. The author dicusses the stylistic nature of the oppositives and analyzes the typology of the contexts, in which they are used.
Keywords: linguistic image of the world; lexical intepretation; concept